Muslim Cosmopolitanism in the Age of Empire - Seema Alavi (Cambridge Harvard University Press, 2015)
Seema Alavi challenges the idea that all pan-Islamic configurations are anti-Western or pro-Caliphate. A pan-Islamic intellectual network at the cusp of the British and Ottoman empires became the basis of a global Muslim sensibility--a political and cultural affiliation that competes with ideas of nationhood today as it did in the last century.
Include Index and Notes
Keywords: Cosmopolitanism -- India -- Islamic countries